2018
DOI: 10.3390/jimaging4120147
|View full text |Cite
|
Sign up to set email alerts
|

Confidence Estimation for Machine Learning-Based Quantitative Photoacoustics

Abstract: In medical applications, the accuracy and robustness of imaging methods are of crucial importance to ensure optimal patient care. While photoacoustic imaging (PAI) is an emerging modality with promising clinical applicability, state-of-the-art approaches to quantitative photoacoustic imaging (qPAI), which aim to solve the ill-posed inverse problem of recovering optical absorption from the measurements obtained, currently cannot comply with these high standards. This can be attributed to the fact that existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…This is especially relevant in deep tissue due to fluence dependent spectral coloring. While there are promising approaches to address these fluence effects in general [29,30,31] and spectral coloring specifically [28], the translation of quantitative PA imaging deep in tissue remains a major challenge. Values are averaged over one minute beginning at the time after start of the recording.…”
Section: Resultsmentioning
confidence: 99%
“…This is especially relevant in deep tissue due to fluence dependent spectral coloring. While there are promising approaches to address these fluence effects in general [29,30,31] and spectral coloring specifically [28], the translation of quantitative PA imaging deep in tissue remains a major challenge. Values are averaged over one minute beginning at the time after start of the recording.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that large multiscale networks are needed to transform the signal into the sought-after PAT image effectively. In early studies by Waibel et al 104 and Gröhl et al, 126 it was shown that using an asymmetric U-Net to reconstruct the PA image directly from raw sensor data is feasible in a limitedview setting. In comparison to a postprocessing approach using a U-Net, it was competitive in terms of mean reconstruction error, but exhibited a higher variance in reconstruction error.…”
Section: Convolutional Approachesmentioning
confidence: 99%
“…In a detailed study, Gröhl et al 126 used U-Nets to estimate the absorption coefficient in various ways. In two fluence-estimation approaches, asymmetric and symmetric U-Nets were used to estimate the fluence map ϕ from time series data g and from initial pressure distribution f, respectively.…”
Section: U-net-based Optical Inversionsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,13,14 One major aspect that has recently gained increasing attention is assessing the reliability of the quantitative results. 15,16 In this paper, we focus on estimating the uncertainty of the SO 2 levels retrieved from spectral fitting, independently of the methods used for OA data acquisition, image reconstruction, or for the correction of spectral distortions. More precisely, we dwell on the fact that fitted SO 2 values that are physiologically reasonable do not necessarily imply that the measured OA spectra follow the trend of real blood spectra.…”
Section: Introductionmentioning
confidence: 99%